Nuclear Medicine for the Orthopedic Foot and Ankle Surgeon. (May 2020) - Serino, Joseph; Kunze, Kyle N.; Jacobsen, Stephen K.; Morash, Joel G.; Holmes, George B.; Lin, Johnny; Lee, Simon; Hamid, Kamran S.; Bohl, Daniel D.
Nuclear medicine has been widely applied as a diagnostic tool for orthopedic foot and ankle pathology. Although its indications have diminished with improvements in and the availability of magnetic resonance imaging, nuclear medicine still has a significant and valuable role. The present article offers a comprehensive and current review of the most common nuclear imaging modalities for the orthopedic foot and ankle surgeon. Methods discussed include bone scintigraphy, gallium citrate scintigraphy, labeled-leukocyte scintigraphy, and single-photon emission computed tomography (SPECT). We review the indications and utility of these techniques as they pertain to specific foot and ankle conditions, including osteomyelitis, stress fractures, talar osteochondral lesions, complex regional pain syndrome, oncology, plantar fasciitis, and the painful total ankle arthroplasty. We conclude with a discussion of our approach to nuclear medicine with illustrative cases. Level of Evidence: Level V, expert opinion.